Surveillance of Tick-borne Disease Pathogens in Ticks in Yamagata Prefecture, Japan - SETO, Junji; HIGASHI, Hideo; TANAKA, Shizuka; KOJO, Nobuaki; NAKAMURA, Yumena; IKEDA, Tatsuya; MIZUTA, Katsumi (Journal of the Japan Veterinary Medical Association, 2020)
To investigate the possibility of tick-borne disease (TBD) occurrence in Yamagata, Japan, we attempted to detect the specific gene of TBD causative pathogens in 158 host-seeking adult ticks and 112 adult ticks biting wild animals in Yamagata from 2016 to 2018. Results revealed that all tick specimens were negative for the pathogens' gene of Japanese spotted fever, Lyme disease, tick-borne relapsing fever, tick-borne encephalitis, and severe fever with thrombocytopenia syndrome, all of which have been reported in Japan. In contrast, the specific gene sequence of Rickettsia helvetica was detected from 30 Ixodes monospinosus and a Haemaphysalis japonica. That of Rickettsia monacensis was detected from an Ixodes nipponensis. Results show that TBD known in Japan might not constitute a serious human health threat in Yamagata, but special attention is required to monitor the occurrence of TBD, including ones that have not been reported in Japan.